2010
DOI: 10.1089/ast.2009.0421
|View full text |Cite
|
Sign up to set email alerts
|

Hygroscopic Salts and the Potential for Life on Mars

Abstract: Hygroscopic salts have been detected in soils in the northern latitudes of Mars, and widespread chloride-bearing evaporitic deposits have been detected in the southern highlands. The deliquescence of hygroscopic minerals such as chloride salts could provide a local and transient source of liquid water that would be available for microorganisms on the surface. This is known to occur in the Atacama Desert, where massive halite evaporites have become a habitat for photosynthetic and heterotrophic microorganisms t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
108
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(113 citation statements)
references
References 52 publications
3
108
0
1
Order By: Relevance
“…Two mechanisms have been suggested for brine formation on Mars: its formation by salts absorbing atmospheric water vapor (deliquescence) when the relative humidity exceeds a threshold value known as the deliquescence relative humidity and the temperature is above the salts' eutectic value (Clark 1978;Rennó et al 2009;Davila et al 2010;Gough et al 2011;Nuding et al 2015;Martín-Torres et al 2015;Nikolakakos and Whiteway 2015), and its formation by salts melting water ice when the temperature exceeds the eutectic value of salts in contact with water ice (Brass 1980;Clark and Van Hart 1981;Fairén et al 2009;. Perchlorate salts, in particular Ca(ClO 4 ) 2 , Mg(ClO 4 ) 2 and Na(ClO 4 ) salts, are extremely relevant for brine formation via deliquescence and melting because they have low eutectic temperatures and were found in polar and equatorial regions Glavin et al 2013), suggesting that they are distributed globally.…”
Section: Liquid Water and The H 2 O Cyclementioning
confidence: 99%
“…Two mechanisms have been suggested for brine formation on Mars: its formation by salts absorbing atmospheric water vapor (deliquescence) when the relative humidity exceeds a threshold value known as the deliquescence relative humidity and the temperature is above the salts' eutectic value (Clark 1978;Rennó et al 2009;Davila et al 2010;Gough et al 2011;Nuding et al 2015;Martín-Torres et al 2015;Nikolakakos and Whiteway 2015), and its formation by salts melting water ice when the temperature exceeds the eutectic value of salts in contact with water ice (Brass 1980;Clark and Van Hart 1981;Fairén et al 2009;. Perchlorate salts, in particular Ca(ClO 4 ) 2 , Mg(ClO 4 ) 2 and Na(ClO 4 ) salts, are extremely relevant for brine formation via deliquescence and melting because they have low eutectic temperatures and were found in polar and equatorial regions Glavin et al 2013), suggesting that they are distributed globally.…”
Section: Liquid Water and The H 2 O Cyclementioning
confidence: 99%
“…observed that intact saline soil cores with surface water potentials of about −41 MPa consumed atmospheric CO, and that surface soil (0-2 cm) from this site oxidized exogenous CO, as did saline soils, sediments, and crusts from three other systems with water potentials consistent with brines that might exist on Mars (33,34). These systems included salinized volcanic ash and sand from Hawai'i Island (water potentials from about −29 to −117 MPa), mixed gypsum and halite deposits from solar salterns in the Atacama Desert, Chile (water potentials of about −8 to −12 MPa), and salt-encrusted sediments from the Bonneville Salt Flats, Utah (BSF; water potentials of about −42 MPa).…”
mentioning
confidence: 72%
“…Zorzano et al (2009) demonstrated that small amounts of sodium perchlorate spontaneously absorb moisture and melt into a liquid solution under martian atmospheric conditions. In addition, Davila et al (2010) reported the deliquescence capacity of hygroscopic salts and their hypothetical capacity to support microbial growth or metabolic activity under simulated martian conditions. Our AtacaMars field campaign demonstrates that subsurface hygroscopic salt environments may be true oasis for microbial life and further supports the possibility of a subsurface martian habitat based on the deliquescence capacity of similar hygroscopic salts.…”
Section: A Hygroscopic Mineral-driven Subsurface Hypersaline Habitat:mentioning
confidence: 99%